Ocotea Cymbarum Kunth. E a Valoração de Residuos Madeireiros para Obtenção de Óleos Essenciais - Reis, Atailson Pereira Vilaça (2023)
In Amazonas, approximately 400 species belonging to 25 genera are found. different from the Lauraceae family, among which Ocotea cymbarum Kunth is present. known as inhamuí laurel, a wood-generating tree widely used by furniture and civil construction. The extraction of essential oils is a practice that has gained prominence in the aromatherapy industry and in the production of natural perfumes, however, the The use of wood residues for essential oil extraction is something little explored. O The objective of this work was to determine the feasibility of using wood waste generated by forestry exploitation with the aim of obtaining an essential oil. From that extraction, we want to analyze whether it is viable to produce it in large quantities with a view to profitability. The samples were in the form of sawdust, which were obtained from a site located on the mission road in the municipality of Tefé. the method adopted for extractions was hydrodistillation, using a Clevenger-type apparatus, extractions followed the same standard and proportion between biomass and water used, for every 50g of plant mass 10g of distilled water was added. The oil was analyzed on a gas chromatograph coupled to a mass spectrometer, model GCMS-QP2010, from Shimadzu, equipped with a J&W DB-5MS fused silica capillary column. The identification of substances was carried out by comparing the mass spectra and linear retention index with those of library of spectra and literature, the trunk and wood chips were used, the yields of essential oils obtained by hydrodistillation in Clevenger ranged from 0.2% to 0.9%, with the trunk being the part of the plant that obtained the highest yield, 0.9%, were sixty-one peaks were detected by the chromatogram, with 57 being identified, which represents 97.07% of the total, the majority components are: Selin-11-em-4-α-ol (14.57%), α-cadinol (6.37%), Rosifoliol (5.03%), Valerianol (4.96%), α Cubebeno (4.93%), δ Cadinene (4.89%) and longiborneol acetate (4.87%). The oil that presented the lowest yield was extracted from wood chips, and obtained a yield of 0.2%, it is mainly composed of Methyl Eugenol (30.68%), Elemycin (11.26%), Asaricin (6.16%) and δ-terpineol (2.53%).Some compounds present present antifungal, pollinating, hepatoprotective and repellents, which demonstrates the biotechnological potential of the species and the bioeconomic potential practice, when exploiting waste to obtain extra income for families in communities riverside